2007
DOI: 10.1783/147118907782101751
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the costs to health systems of unsafe abortion: a comparison of four strategies

Abstract: Background and methodology Strategies to reduce health systems costs of providing abortion and post-abortion care while simultaneously improving quality of care are well documented but infrequently applied. We created 'Savings', a spreadsheet-based tool that allows policymakers and other stakeholders to estimate and compare the feasibility and sustainability of different strategies of providing abortion and post-abortion care. By applying cost data primarily from Uganda, we showed the per-case costs under four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 11 publications
0
42
0
2
Order By: Relevance
“…A recent study in Nigeria 10 estimated that the cost of contraceptive services to prevent unwanted pregnancies would have been only one-fourth of that expended in treating postabortion complications. Another study 21 showed that the cost of obtaining a safe abortion in Uganda was between $6 and $23, compared to the average cost of $89 that we calculated for treating a postabortion complication in Sub-Saharan Africa. Furthermore, a global study on the costs and benefits of reducing unmet need for contraception estimated that, in Sub-Saharan Africa in 2003, eliminating this unmet need would have cost about US$1 billion for additional contraceptive services, while averting 10.5 million unintended *The authors derived this figure using the United Nations Population Fund's Reproductive Health Costing Tool (<http://www.who.int/pmnch/ topics/economics/costing_tools/en/index15.html>).…”
Section: Discussionmentioning
confidence: 72%
“…A recent study in Nigeria 10 estimated that the cost of contraceptive services to prevent unwanted pregnancies would have been only one-fourth of that expended in treating postabortion complications. Another study 21 showed that the cost of obtaining a safe abortion in Uganda was between $6 and $23, compared to the average cost of $89 that we calculated for treating a postabortion complication in Sub-Saharan Africa. Furthermore, a global study on the costs and benefits of reducing unmet need for contraception estimated that, in Sub-Saharan Africa in 2003, eliminating this unmet need would have cost about US$1 billion for additional contraceptive services, while averting 10.5 million unintended *The authors derived this figure using the United Nations Population Fund's Reproductive Health Costing Tool (<http://www.who.int/pmnch/ topics/economics/costing_tools/en/index15.html>).…”
Section: Discussionmentioning
confidence: 72%
“…[53][54][55] Major physiological, financial and emotional costs are also incurred by the women who undergo unsafe abortion. 72 A study 56 found that the cost of management of abortion is lower in a legal setting that allowed elective abortion than in the restrictive legal setting. The cost also reduces when making services accessible at all service levels.…”
Section: Health Consequences Of Unsafe Abortion and Impact On Health mentioning
confidence: 99%
“…Postabortion care services have improved, 9-11 but deaths and suffering from unsafe abortion continue to occur, even though they are preventable with the appropriate information, education, training, technology and political commitment. Treating the complications of unsafe abortion often requires surgery, expensive drugs and supplies, and prolonged hospital stays, [12][13][14][15][16] and the cost of treating a septic abortion is estimated to be four times that of an assisted delivery. 12 In some developing countries, treating complications of unsafe abortion consumes up to 60% of the total annual budget for gynecologic care.…”
Section: Caring For Women With Abortion Complications In Ethiopia:natmentioning
confidence: 99%